2011
DOI: 10.26719/2011.17.10.744
|View full text |Cite
|
Sign up to set email alerts
|

744 Predictive value of plasma haematocrit level in early diagnosis of pre-eclampsia

Abstract: While pre-eclampsia is the most common complication of pregnancy, a definitive screening test for early diagnosis is still elusive. In this study, haematocrit value was assessed as a screening test for pre-eclampsia in 660 women at 24-28 weeks of pregnancy attending a hospital in Tehran, Islamic Republic of Iran. Mean haematocrit values were significantly higher in pre-eclamptic than non-pre-eclamptic women: 37.7% (SD 2.0%) and 35.9% (SD 1.7%) respectively. The receiver operating characteristics curve showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…This may, therefore, be considered as an indicator for detection of preeclampsia. 5 However, in the present study, hemoglobin and PCV did not differ significantly between the two groups; this is in agreement with two studies that reported hemoglobin and hematocrit to be poor indicators. 2,6 Conflicting results were observed in a study by Monteiro et al 1 who observed that hypertensive mothers with IUGR and IUD of fetus had significantly lower hemoglobin concentration and PCV compared with those mothers with normal fetus.…”
Section: Discussionsupporting
confidence: 93%
“…This may, therefore, be considered as an indicator for detection of preeclampsia. 5 However, in the present study, hemoglobin and PCV did not differ significantly between the two groups; this is in agreement with two studies that reported hemoglobin and hematocrit to be poor indicators. 2,6 Conflicting results were observed in a study by Monteiro et al 1 who observed that hypertensive mothers with IUGR and IUD of fetus had significantly lower hemoglobin concentration and PCV compared with those mothers with normal fetus.…”
Section: Discussionsupporting
confidence: 93%
“…After assessed, we found that only the PT plasma level had a significantly statistical difference among TT, CT and CC groups of the two polymorphisms of IL-1β (forIL-1β-31C/T: F = 1.644, P = 0.01; for IL-1β -511T/C: F = 1.587, P = 0.016). Moreover, previous researches had indicated that hematocrit, platelet counts and indices and the Mean platelet volume (MPV) were useful as screening test for early diagnosis of PE [29][31]. Basing on the above results, PT level in plasma may be regarded as a marker of the genotype, which needs to be clarified by further studies.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of this pathophysiologic pathway is in line with the reported increased serum concentrations of atrial natriuretic peptide ( 52 ) and copeptin/vasopressin in PE ( 53 ) and with the impaired expansion of maternal plasma volume in EPE ( 9 ). The early gestational onset of this phenomenon is also supported by the shallow, but significant, rise of serum hemoglobin concentrations and hematocrit in the first trimester of pregnancies destined to develop EPE ( 31 , 54 , 55 ) but not in those eventually leading to FGR ( 56 ). As explained above and illustrated in Figure 1 , FGR pregnancies show a normal rise of plasma volume and total body water, superimposed upon constitutionally low body water already present before conception.…”
Section: Pathways Of Maternal Low Volume Circulation In Early Onset P...mentioning
confidence: 89%